Prediction of absolute bioavailability of medicines in children: based on predicted pediatric clearance from adults - Iftekhar Mahmood (Exploration of Drug Science)
Aim: The objective of this study was to evaluate the predictive performance of a proposed method to predict absolute bioavailability of medicines in children (infants to adolescents). Methods: From the literature, systemic and oral clearances as well as absolute bioavailability values for 15 medicines (28 observations across different age groups) from infants to adults were obtained. Systemic and oral clearances of these medicines in children were predicted using age-dependent exponent (ADE) allometric model using observed adult clearance values. Then using the predicted clearance values, absolute bioavailability was predicted in children. The predictive performance of the proposed method was evaluated by comparing the predicted absolute bioavailability of the studied medicines with the observed absolute bioavailability in children. Results: The results of the study indicated that the ADE model provided a good prediction of systemic and oral clearances in children from adult clearance values [89% and 82% observations within 0.5–1.5-fold prediction error following intravenous (IV) and oral administration, respectively]. The predicted absolute bioavailability by the proposed method was within 0.5–1.5-fold prediction error for 93% observations. Conclusions: This study indicated that it was possible to estimate absolute bioavailability of medicines in children with acceptable accuracy (within 0.5–1.5-fold prediction error) by the proposed method. The estimated absolute bioavailability in children could be useful in designing a first-in-children dose during pediatric drug development.